Ideological conditionings of the social protest criminalization and the support to democracy in a Lima sample - Rottenbacher, Jan Marc (2013)
The influence of right-wing political conservatism on support for democracy and the criminalization of social protest is analyzed in a sample of university students from the city of Lima (N = 201). As indicators of the right-wing political conservatism, measures of right-wing authoritarianism (RWA), social dominance orientation (SDO) and right-wing political orientation were used. Two path diagrams were proposed: the second diagram showed a proper degree of fit and proposes a positive covariance between RWA, SDO and right-wing political orientation. The diagram also suggests that RWA, SDO and right-wing political orientation exert a direct influence on the criminalization of social protest, while SDO and RWA exert an indirect influence on support for democracy. Finally, support for democracy present an inverse correlation with the criminalization of social protest.